CPIA Africa, August 2020 : Safeguarding Human Capital during and beyond COVID-19 - World Bank (World Bank, Washington, DC, 2020)
The 2020 Africa Country Policy and Institutional Assessment (CPIA) report covers the period from January to December 2019. The addition of Somalia brought the number of the region’s International Development Association (IDA)–eligible countries to 39. The overall CPIA score for the region’s 39 IDA-eligible countries came in at 3.1, the same as in the previous three years, in a context of moderating per capita growth. The average scores for most of the CPIA clusters trended down in 2019. While the average score for the economic management cluster was unchanged from last year’s assessment, the average scores for the other three clusters—structural policies, social inclusion, and public management and institutions—declined, indicating that the quality of policies and institutions in the region’s IDA countries weakened in 2019. The weakening of structural policies was reflected in the decline in the quality of trade policy, uneven improvements in the regulations affecting factor and product markets, and further deterioration of the financial sector performance. In the area of social inclusion, many countries experienced a decrease in the quality of service delivery that affects access to and quality of health and education services. In the broader area of governance, limited progress was made in strengthening property rights, and transparency and accountability. In addition, the quality of public administration declined, and financial management systems and revenue mobilization capacity weakened in many countries.